Human Resource Development Factors Among Civil Services Employees In Ministry Of Health, Gaza Strip Palestine - Ahmad, Shaqfa Khalil Mustafa (2014)

(untitled)
Human resource development (HRD) can be influenced by many dimensions aside from those in the definitions of HRD, where common central factors focus on the skills and abilities of employees. In addition, the activities are aimed at achieving the organizational goals of increasing productivity. Bentuk pembangunan sumber manusia (PSM) boleh dipengaruhi oleh banyak dimensi sebagai tambahan kepada definisi PSM itu sendiri. Biasanya, faktor-faktor utama yang menjadi fokus adalah kemahiran dan kebolehan kakitangan.